Modeling of scenarios for the underground construction planning based on the foresight and cognitive modeling methodologies - Pankratova, N.D.; Pankratov, V.A. (Reports of the National Academy of Sciences of Ukraine, 2021)
The modeling of scenarios for the underground construction planning is based on the mathematical support of fore sight methodology aimed at the creation of alternative scenarios and the cognitive modeling to build scenarios for the development of a desired future and ways of their implementation. We propose to use these methodologies together: the results obtained at the stage of the foresight methodology should be used as initial data for the cognitive modeling. Using the foresight process at the first stage of modeling allows us, with the help of expert assessment procedures, to identify critical technologies and to construct the alternatives of scenarios with quantitative characteristics. For the justified implementation of a particular scenario, the cognitive modeling allows one to build causal relationships with the consideration of a large number of interconnections and interdependences. The developed strategy is applied to the study of underground construction objects in order to select reasonable scenarios for their future development.